The individual zones of optimal functioning (IZOF) model (1978-2014): Historical overview of its development and use - Ruiz, M. C.; Raglin, J. S.; Hanin, Y. L. (International Journal of Sport and Exercise Psychology, 2015)
The individual zones of optimal functioning (IZOF) model is a sport-specific framework that describes the relationship between emotional experiences and relative success in sporting tasks on the basis of individual rather than group-based patterns. Initially developed by the psychologist Juri Hanin in the 1970s, the number of published studies using the model has since significantly grown and diversified. In an effort to create a comprehensive database of IZOF research and reviews, a literature search was conducted using several databases and existing reference lists. This analysis yielded a total of 183 IZOF-based publications (from 380 compiled). The list of publications was subdivided into several categories including general reviews (N = 25), assessment and methodology (N = 13), peer-reviewed and research papers involving samples ranging from elite athletes to physical education students (N = 120). Twenty-five studies were related to communication or interpersonal relationships, coaching and optimisation of performance. Future IZOF research directions will focus on multimodal profiling of athletes` performance-related emotional and non-emotional experiences, and assessment of individually optimal performance. The individual zones of optimal functioning (IZOF) model (1978-2014): Historical overview of its development and use. Available from: https://www.researchgate.net/publication/276831504_The_individual_zones_of_optimal_functioning_%28IZOF%29_model_%2819782014%29_Historical_overview_of_its_development_and_use [accessed May 28, 2015].